Makna Falsafah Budaya Tallu Lolona - Stefanus Sapri (Melo: Jurnal Studi Agama-agama, 2022)
Culture is the essence of human life. Therefore, humans are often called cultural creatures because being cultured is a task from God. Humans as creatures who have reason and can think must be the main actors in their environment where they have to live to be responsible for maintaining and caring for other creations that are around them. Tallu Lolona philosophy is understood as the three pinnacles of human life, namely lolo tau (humans), lolo tananan (plants), and lolo patuoan (animals). This philosophy is highly respected by the Toraja people, even the tallu lolona philosophy depicts the gospel values ​​that the Toraja people live by, such as peace, brotherhood, etc. The description in this paper focuses on the meaning of Tallu Lolona's cultural philosophy from the perspective of Christian faith. With literature study research methods and cursory observations on the results that the philosophy of tallu lolona has a meaning that is highly valued and upheld by the Toraja people including Christians because the philosophy of tallu lolona is a philosophy that has very important goals and meanings for people's lives.